The average value of mean arterial pressure among children aged 3-10 years as per age, gender and height centiles: A cross sectional study - Naushad, Aleena; Anand, Manjula; Kumar, Satish; M. R., Anand; E. K., Suresh Kumar (International Journal of Contemporary Pediatrics, 2023)
Background: Objective of the study was to find out the average MAP among children aged between 3-10 years based on age, gender and height centiles and to study the correlation of MAP with weight, height and BMI. Methods: A total of 502 children were included in the study. First the demographic details of the children was collected. Then anthropometric parameters were measured. Systolic BP, Diastolic BP and MAP were recorded. SPSS version 20 was used for statistical analysis. Results: MAP has got a positive correlation with weight, height and BMI. Conclusions: The mean MAP of male children, 3-4 years 75±9 mmHg, 5-6 years 75±8 mmHg, 7-8 years 76±7 mmHg, 9-10 years, 79±11 mmHg. The mean MAP of female children, 3-4 years 77±7 mmHg, 5-6 years 77±8 mmHg, 7-8 years 78±9 mmHg, 9-10 years, 79±8 mmHg. MAP was found to be highly correlated with weight, height and BMI.